Pembuatan Teskit Boraks dalam Upaya Efisiensi Penggunaan Bahan dan Alat Laboratorium - S Sulistyawati; Widyaningsih Wiyati (Jurnal Pengelolaan Laboratorium Pendidikan, 2020)
Borax is a carcinogenic compound which is dangerous to the body. The flame method is one of the qualitative laboratory testing that usually used to determine the Borax compound in food. The method not only needs H2SO4, methanol, furnace equipment which is prices, but also needs long time because of the graying process. The research aims to make a simple borax test kit (simple method) by extracting anthocyanin substances on the skin of purple sweet potatoes and testing the borax compound in food samples. Materials and tools used are purple sweet potato skin, 96% ethanol, filter paper, knives, cutting boards, measuring cups, beaker glass, food scales and petri dishes. The results of the borax test kit that have been made are then tested using the borax standard as the gold standard and it showed that there was color changing of the test kit, i.e from pink to blue. The borax test kit was also tested on four food samples that possibly contained borax, i.e gendar crackers, white tofu, meatballs and noodles. Gendar crackers was the only food sample that contain borax. Therefore, it was concluded that the borax test kit made from filter paper containing anthocyanin can be used as an alternative tool in qualitatively testing of borax in food